Clinicians' challenges in managing patients with invasive fungal diseases in seven Asian countries: An Asia Fungal Working Group (AFWG) Survey. (June 2020) - Tan, Ban Hock; Chakrabarti, Arunaloke; Patel, Atul; Chua, Mitzi Marie M.; Sun, Pei-Lun; Liu, Zhengyin; Rotjanapan, Porpon; Li, Ruoyu; Wahyuningsih, Retno; Chayakulkeeree, Methee; Chen, Yee-Chun; ,
Highlights: The majority of Asian physicians managing fungal infections do not have formal training in medical mycology. Despite this, >80% do not use the services of an ID physician. Laboratory support for mycology is not widespread – barely two-thirds have access to the galactomannan assay, and only a quarter have access to azole therapeutic drug monitoring. The majority of physicians managing an invasive fungal infection could not use the drug of choice because of cost, though most claimed to follow international guidelines. Abstract: Background: Invasive fungal diseases (IFD) are a serious threat, but physicians in Asia lack access to many advanced diagnostics in mycology. It is likely that they face other impediments in the management of IFD. A gap analysis was performed to understand the challenges Asian physicians faced in medical mycology. Methods: The Asia Fungal Working Group (AFWG) conducted a web-based survey on management practices for IFD among clinicians in China, India, Indonesia, Philippines, Singapore, Taiwan and Thailand. Findings: Among 292 respondents, 51.7% were infectious disease (ID) specialists. Only 37% of respondents had received formal training in medical mycology. They handled only around 2–4 proven cases of each fungal infection monthly, with invasive candidiasis the most common. For laboratory support, the majority had access to direct microscopy (96%) and histopathology (87%), but galactomannan and azole levels were available to 60% and 25% of respondents, respectively. The majority (84%) used clinical parameters for treatment response monitoring, and 77% followed the Infectious Diseases Society of America guidelines. The majority (84%) did not use the services of an ID physician. Where febrile neutropenia was concerned, 74% of respondents used the empirical approach. Only 30% had an antifungal stewardship program in their hospital. Eighty percent could not use preferred antifungals because of cost. Interpretation: The survey identified inadequacies in medical mycology training, non-culture diagnostics, access to antifungal drugs, and local guidelines as the major gaps in the management of IFDs in Asian countries. These gaps are targets for improvement.